Assessment of the effect of the devolved governance intervention on early childhood development and education in Samburu County - Kasaine, Moses (Strathmore University, 2021)
The 2010 Constitution bestowed Early Childhood Education Development to the devolved units. Despite this, there are challenges that exist which hinder accessibility to schools. This study sought to assess the effect of devolution on enrolment to early childhood development and education. The specific objectives were to establish the effect of community infrastructural development, impact of county government investment on school facilities, introduction of school feeding program, effect of teaching staff on enrolment to ECDE in the advent of devolution. The study was guided by the theory of change. The descriptive design was adopted. The research targeted 530 ECDE teachers. The sample size was 30% of all teachers, which was 159. The data was analyzed using descriptive statistics including frequency distribution, measures of central tendencies (mean and standard deviation). A correlation analysis was used to determine the level of association of variables, while regression analysis was used to establish the relationship between the study variables. The study outcomes revealed a positive and significant relationship between number of classrooms and ECDE enrolment, and number of teachers and ECDE enrolment. The study concluded that the introduction of devolution had led to new infrastructural developments within Samburu County, the county government investment on school facilities was effective in enhancing enrolment to ECDE., the introduction of devolution has resulted to increase in the number of feeding programs in the ECDE centers, and that the introduction of devolution has resulted to hiring of more permanent ECDE teachers. Based on study results, the research recommended that both levels of governments should invest more in infrastructural development, improvement of school facilities, and school feeding programs. Finally, the county government should employ more teachers to ECDE centers.
Submitted in partial fulfilment of the requirements for the degree of Master of Public Policy and Management at Strathmore University
Keywords: Early Childhood Education; Evolution--enrolment--Kenya; ECDE Enrolment